Study the Effect of Annealing on the Structural Properties of Zinc Oxide Films by Electrolysis Technique - A. Mahdi, Aws; A. Makki, Sameer (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Zinc oxide films (ZnO) are prepared by an electrolysis technique and without vacuum and then annealed atvarious temperatures (300,400,500)OC for an hour. The structural analysis performed by X-Ray diffraction (XRD) shows,dominant orientation of this films is plane (101), has a hexagonal structure and  polycrystalline pattern and it was is found that the crystal size increases(24,29) nm at annealing temperatures (300, 400)Â° C, but the crystal size decreases to (20 nm) at annealing temperature (500 Â° C). As the results of a surface nature study of these films showed by examining the atomic force microscope (AFM), the grain  size increases from (60.79 to 88.11) nm, and the surface roughness increases from  (1.99 to 2.34) nm when increasing annealing temperatures is (300,400,500)Â°C, respectively.